Identification of Gastrointestinal Protozoa of Sumatera Elephant (Elephas maximmus sumatranus) in Lombok Wildlife Park - Fernando Jose Immanuel Clinton Situmorang; Kholik Kholik; Candra Dwi Atma; Katty Hendriana Priscilia Riwu; Iwan Doddy Dharmawibawa; Munawer Pradana (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The protozoan parasites have been reported to infect Sumatran elephants. Gastrointestinal protozoa could potentially be a factor in the decline in the Sumatran elephant population in Indonesia. This study aims to identify the presence of gastrointestinal protozoa in Sumatran Elephant (Elephas maximus sumatranus) in the Lombok Wildlife Park, North Lombok Regency, Indonesia. This research has used fresh fecal samples from 5 Sumatran elephants. The examination of feces samples using native, sedimentation, and floating methods. The research results have identified the presence of gastrointestinal protozoa in 2 of the 5 Sumatran elephant feces examined. The gastrointestinal protozoa found were Eimeria spp with dimensions of 16.30 x 20.93 μm and 25.21 x 38.49 μm.